1994
DOI: 10.1007/bf02393867
|View full text |Cite
|
Sign up to set email alerts
|

Forest product use at an upper elevation village in Nepal

Abstract: / This paper describes forest product use at Chimkhola, an upper elevation village of west central Nepal. Villagers have large herds of livestock that they use to fertilize agricultural fields by holding the animals on cropland for one to several weeks prior to planting. Herds are moved sequentially from one group of fields to another until all are planted, and then families take animals into the forests. Herders, therefore, live in temporary shelters away from the homestead throughout the year, and for much o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…Our findings confirm the importance of environmental income to rural households in the Western Himalayan region of Nepal, matching that of similar studies [11,49]. Environmental income mainly originated from the collection of environmental products consumed in households (subsistence).…”
Section: Rural Roads and Environmental Income In The Nepal Himalayassupporting
confidence: 91%
“…Our findings confirm the importance of environmental income to rural households in the Western Himalayan region of Nepal, matching that of similar studies [11,49]. Environmental income mainly originated from the collection of environmental products consumed in households (subsistence).…”
Section: Rural Roads and Environmental Income In The Nepal Himalayassupporting
confidence: 91%
“…Subsistence fuel wood consumption is highest in areas with high forest cover, fuel wood access, lack of alternative energy sources, cold climatic seasons, use of open fires, and culturally determined uses of fuel wood, e.g., for religious celebrations. In such locations, for example, in the Himalayas (Metz, 1994) or Northern China (Démurger & Fournier, 2011) We assessed the overall representativeness of the PEN study sites at two scales. We first compared the regions from which cases were selected using administrative jurisdictions equivalent to the "province" level (Dewi, Belcher, & Puntodewo, 2011).…”
Section: S24mentioning
confidence: 99%
“…Chimkhola has a summer monsoonal climate, with a mean annual precipitation of 2700 mm and mean monthly temperatures ranging from 6°C in January to 29°C in June (Metz 1989). Metz (1989Metz ( , 1990Metz ( , 1994 found that 84% of Chimkhola's 285 families engaged in the goTh system of resource use. The average goTh hut was 3.5 m × 7.0 m, with an additional narrow fenced area attached to the front (see Figure 1).…”
Section: Study Areamentioning
confidence: 99%